2023
DOI: 10.1088/1742-6596/2623/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Teaching Modules with Problem-Based Learning (PBL) Model Assisted by E-Book to Improve Problem-Solving Skills on Renewable Energy Material and Implementation of Independent Learning Curriculum

Dwikoranto,
I R Dawana,
R Setiani

Abstract: Problem-solving skills are an important basic competency in 21st-century learning through the Merdeka Belajar Curriculum. However, the problem-solving skills of students in Indonesia are still low. Therefore, an effective learning model is needed to improve problem-solving skills, one of which is through the development of teaching modules. This study aims to develop teaching modules based on Problem-Based Learning (PBL) assisted by e-books to improve the problem-solving skills of grade X high school students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(66 reference statements)
0
1
0
1
Order By: Relevance
“…The results of teacher responses obtained a percentage of 100% in the very appropriate category and student responses obtained a percentage of 97% in the very appropriate category. Previous research findings also state that the use of e-books based on Problem-Based Learning is very suitable for use in learning (Dwikoranto et al 2023;Herdianto et al 2021). It can be concluded that e-books based on Problem-Based Learning are very suitable for use in learning.…”
Section: Feasibility Of E-books Based On Problem Based Learningmentioning
confidence: 86%
“…The results of teacher responses obtained a percentage of 100% in the very appropriate category and student responses obtained a percentage of 97% in the very appropriate category. Previous research findings also state that the use of e-books based on Problem-Based Learning is very suitable for use in learning (Dwikoranto et al 2023;Herdianto et al 2021). It can be concluded that e-books based on Problem-Based Learning are very suitable for use in learning.…”
Section: Feasibility Of E-books Based On Problem Based Learningmentioning
confidence: 86%
“…Strategi merupakan faktor terpenting yang diminati guru dalam pelaksanaan pembelajaran, karena strategi pembelajaran yang digunakan guru mempengaruhi keberhasilan belajar mengajar (Daud, 2020). Ada beberapa macam strategi pembelajaran, diantaranya strategi pembelajaran pendekatan kelompok dan strategi pembelajaran pendekatan individual.…”
Section: Hasil Dan Pembahasanunclassified